Validation of a Simulated Commercial Plain Bagel Baking Process and Thermal Resistance Characterization of a 5-Strain Shiga Toxin-Producing Escherichia coli When Introduced via Flour - Conor Hunt; Arshdeep Singh; Drushya Ramesh; Lakshmikantha H. Channaiah (Foods)
A study was conducted to validate the plain bagel baking process as an effective kill-step in controlling Shiga toxin-producing Escherichia coli (STEC) in the event of pre-baking contamination originating from flour. Unbleached bread flour was inoculated with five strains of STEC and dried back to its original water activity levels. The inoculated flour was used to prepare the bagel dough, proofed, boiled for 2 min, and baked at 232.2 °C (450 °F) for 14 min mimicking the commercial manufacturing process. Additionally, water activity (aw) and pH in plain bagels during baking, and thermal inactivation kinetics (D- and z-values) of STEC in plain bagel dough were studied. The results clearly demonstrated that baking plain bagels at 232.2 °C (450 °F) for 14 min will result in at least a >5 log reduction in the STEC population, thus providing an effective kill-step assuring the safety of the finished food products. The pH of plain bagels increased significantly from pre-proofed plain bagel dough to seven min into the baking process, reaching a final value of 5.83. The water activity of the crust and crumb portions of plain bagels was significantly different during the baking process. The D-values of STEC in plain bagels at, 56, 59, and 62 °C were 26.3 ± 1.55, 9.0 ± 0.27, and 2.50 ± 0.15 min with a z-value of 5.8 ± 0.16 °C.